Early Age of Cannabis Initiation and Its Association With Suicidal Behaviors - Manik Ahuja; Manul Awasthi; Suzanna Gim; Kathie Records; Johanna Cimilluca; Kawther Al-Ksir; Johnathan Tremblay; Riddhi P Doshi; Thiveya Sathiyasaleen; Praveen Fernandopulle (Substance Abuse: Research and Treatment, 2022)
Background: Suicide rates in the U.S. have continued to rise over the last 2 decades. The increased availability and broader legalization of cannabis is a public health concern, particularly among adolescents. The objective of this study was to examine the association between the age of cannabis initiation and lifetime suicidal ideations and attempts in a sample of adults aged 18 or older. Methods: Data are from the Collaborative Psychiatric Epidemiology Surveys (CPES), 2001 to 2003 (N = 15 238). The primary objective of the CPES was to collect data about the prevalence of mental disorders, impairments associated with these disorders, and their treatment patterns from representative samples of majority and minority adult populations in the U.S. Logistic regression analyses were conducted to test the association between cannabis initiation age (early ⩽14 years old; later >14 years old) and outcomes of lifetime suicide ideation and attempts. Cigarette use, cannabis use, gender, income, race, education, and age were controlled for the analyses. Results: Overall, 12.5% of participants reported suicide ideation, while 4.2% reported attempt. Early cannabis use was associated with a higher risk of suicide ideation (AOR = 3.32, 95% CI [2.75, 3.80]) than later cannabis use (AOR = 2.15, 95% CI [1.92, 2.39]). Early cannabis use was associated with a higher risk of suicide attempt (AOR = 4.38, 95% CI [3.48, 5.52]) than later cannabis use (AOR = 2.56, 95% CI [2.14, 3.06]). Wald chi-squared tests revealed significant differences between the early and late initiation for both ideation (χ 2  = 26.99; P  < .001) and attempts (χ 2  = 26.02; P  < .001). Conclusions: Significant associations were found between early initiation of cannabis and suicide behaviors. As suicide rates continue to rise, it is recommended that clinicians, treatment providers, and other professionals consider the use of cannabis at an early age as a risk for subsequent suicide behaviors.